Effect Of Internal Marketing In Procurement Strategy Implementation: A Case Study In General Company For Electronic Systems - Sarah Majid Hussein Al Dhahab; Sarmad Hamza Jassim (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The intellectual framework of study depends on two variables represented by ( Internal marketing (IM) , Procurement strategy(PS)) and possibility of its application in Iraqi environment of new light congestion, accelerating and turbulent global changes, which directed the researcher to identify the impact of (IM)on the General Company for Electronic Systems and the extent of its contribution to the implementation of the procurement strategy through main axes Represented by (Procurement as needed strategy, Procurement and manufacturing strategy) and in light of this came the problem of study that researcher framed by adopting the preliminary exploratory study that she conducted for the study community, which suffers from apparent weakness in adopting internal marketing and its lack of knowledge of the role it plays and its employment in application of (PS). Where an intentional sample of (87) principals was chosen, distributed on a number of administrative levels. Descriptive statistical of questionnaire , to achieve this It has two main hypotheses, and (6) sub-hypotheses were branched from them, and they were tested using (SPSS) and a set statistical methods (Spear-Man rank correlation coefficient, simple and multiple linear regression), and the researcher through a set of conclusions, perhaps most prominent of which that there a significant effect of (IM) in application of (PS).